2020
DOI: 10.3389/fped.2020.574014
|View full text |Cite
|
Sign up to set email alerts
|

Higher Hospitalization Rate for Lower Airway Infection in Transfusion-Naïve Thalassemia Children

Abstract: Few studies have addressed the risk of infection in transfusion-naïve thalassemia patients. We aimed to investigate whether transfusion-naïve thalassemia population has higher hospitalization rates for lower airway infection-related diseases than non-thalassemia population in children. A nationwide population-based retrospective cohort study was conducted using detailed medical records of the Taiwan National Health Insurance Research Database. Transfusion-naïve thalassemia patients were compared with a matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Regarding the possible mechanism of thalassemia in children with higher risk of asthma, Palma-Carlos et al [ 21 ] stated that the hemorheological changes in thalassemia include greater rigidity of red blood cells in the capillary bed, which can contribute to changes in bronchial circulation and bronchial hyperactivity yet without solid evidence. Recently, we found that thalassemic patients had a higher incidence of low respiratory tract infection [ 35 ], which may be linked to a higher incidence of asthma or asthma exacerbation [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the possible mechanism of thalassemia in children with higher risk of asthma, Palma-Carlos et al [ 21 ] stated that the hemorheological changes in thalassemia include greater rigidity of red blood cells in the capillary bed, which can contribute to changes in bronchial circulation and bronchial hyperactivity yet without solid evidence. Recently, we found that thalassemic patients had a higher incidence of low respiratory tract infection [ 35 ], which may be linked to a higher incidence of asthma or asthma exacerbation [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%